Validation of self reported diagnosis of hypertension in a cohort of university graduates in Spain - Beunza Juan; Alonso Alvaro; Delgado-Rodríguez Miguel; Martínez-González Miguel (BMC, 2005)
Abstract Background The search for risk factors of hypertension requires the study of large populations. Sometimes, the only feasible way of studying these populations is to rely on self-reported data of the outcome. The objective of this study was to evaluate validity of self-reported diagnosis of hypertension in a cohort of university graduates in Spain. Methods The Seguimiento Universidad de Navarra (SUN) Study is a cohort of more than 15,000 university graduates in Spain. We selected a random sample of 79 cohort participants who reported a diagnosis of hypertension and 48 participants who did not report such diagnosis (76% participation proportion). Then, we compared information on the self-reported diagnosis of hypertension and hypertension status as assessed through two personal blood pressure measurements and an interview. Additionally, we compared self-reported and measured blood pressure levels with intraclass correlation coefficients and the survival-agreement plot. Results From those 79 reporting a diagnosis of hypertension, 65 (82.3%, 95% CI 72.8-92.8) were confirmed through conventional measurement of blood pressure and the interview. From those 48 that did not report a diagnosis of hypertension, 41 (85.4%, 95% CI 72.4-89.1) were confirmed as non hypertensives. Results were similar among men and women, but were worse for overweight and obese individuals, and for those with a family history of hypertension. The agreement between self-reported and measured blood pressure levels (as a continuous variable), as estimated by the intraclass correlation coefficient, was 0.35 for both systolic and diastolic blood pressure. Conclusion Self-reported hypertension among highly educated participants in a cohort study is a relatively valid tool to assess the hypertensive status of participants. However, the investigators should be cautious when using self-reported blood pressure values.